Identifikasi Jenis Tumbuhan Obat di Kecamatan Tanah Pinem Kabupaten Dairi - Sandika, Sahril; Putra, Nanang (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Specifically, the use of medicinal plants for natural medicine is carried out by the people of Tanah Pinem District, Dairi Regency. There are still some people who use plants as natural traditional medicine, but the people around Tanah Pinem District are currently switching to more modern medicine because it is more efficient. The aim of the research is to identify the types of medicinal plants found in Tanah Pinem District and analyze how much public knowledge there is about the types of medicinal plants used. This research is classified as exploratory descriptive research. In this research, the informants used were 10 people each from 3 villages. 1 resource person is a midwife as caretaker, while the other 29 resource persons are village residents aged ± 40 - 60 years. Data was collected through surveys and direct interviews. The data is then analyzed and then presented through tables and diagrams. The research results showed that people in Tanah Pinem District had sufficient understanding of medicinal plants. The results of the survey carried out found 32 species of medicinal plants used for traditional medicine by the community in Tanah Pinem District, Dairi Regency.